Produktivitas Kerja pada Guru: Apakah Dipengaruhi oleh Motivasi Kerja, Disiplin, dan Lingkungan Kerja? - Wahyudi, Widi; Rizki, Ainur (PT Hakhara Akademia Indonesia, 2023)
This study aims to determine the effect of work motivation, discipline and work environment on work productivity teachers at SMK Al-Makmur. The population in this study were teachers of SMK Al-Makmur. The sample used was 31 respondents. The technique used for sampling is a non-probability sampling technique with a saturated sample technique. Data collection used the distribution of questionnaires to teachers of SMK Al-Makmur. The data analysis technique used is multiple linear regression analysis with data processing tools SPSS software version 29. The results of this study indicate that work motivation (X1) has a negative and significant effect on work productivity, while discipline (X2) has no effect on work productivity and work environment (X3) has no effect on work productivity.